The Politics of Judicial Reform in the Democratic Transition: An Analysis of the Chilean Case - Galleguillos Portales, Nibaldo H. (CIENCIA ergo-sum, 2017)
This article examines the difficulties faced by the civilian administrator that replaced the 17-year old military government of general August Pinochet in their effort to dismantle the authoritarian enclaves established in the 1980 constitution. Its focus is on analysis of the strategies pursued by these democratic governments in their quests to reform one such enclave: the judicial power, more specifically, the efforts at replacing some of the members of, as well as taking away some of the political powers of the Suprema Court in order to restore the balance of power characteristics of a democratic political system